Arabidopsis EMB1990 Encoding a Plastid-Targeted YlmG Protein Is Required for Chloroplast Biogenesis and Embryo Development - Chen, Hongyu; Li, Shuqin; Li, Lu; Hu, Hengjin; Zhao, Jie (Frontiers in Plant Science, 2018)
In higher plants, embryo development originated from fertilized egg cell is the first step of the life cycle. The chloroplast participates in many essential metabolic pathways, and its function is highly associated with embryo development. However, the mechanisms and relevant genetic components by which the chloroplast functions in embryogenesis are largely uncharacterized. In this paper, we describe the Arabidopsis EMB1990 gene, encoding a plastid-targeted YlmG protein which is required for chloroplast biogenesis and embryo development. Loss of the EMB1990/YLMG1-1 resulted in albino seeds containing abortive embryos, and the morphological development of homozygous emb1990 embryos was disrupted after the globular stage. Our results showed that EMB1990/YLMG1-1 was expressed in the primordia and adaxial region of cotyledon during embryogenesis, and the encoded protein was targeted to the chloroplast. TEM observation of cellular ultrastructure showed that chloroplast biogenesis was impaired in emb1990 embryo cells. Expression of certain plastid genes was also affected in the loss-of-function mutants, including genes encoding core protein complex subunits located in the thylakoid membrane. Moreover, the tissue-specific genes of embryo development were misexpressed in emb1990 mutant, including genes known to delineate cell fate decisions in the SAM (shoot apical meristem), cotyledon and hypophysis. Taken together, we propose that the nuclear-encoded YLMG1-1 is targeted to the chloroplast and required for normal plastid gene expression. Hence, YLMG1-1 plays a critical role in Arabidopsis embryogenesis through participating in chloroplast biogenesis.